RENEWAL OF ‘ILM AL-KALĀM IN THE CONTEMPORARY ERA: A STUDY OF ṬAHĀ ‘ABDURRAḤMĀN’S METATHEOLOGICAL CONCEPT - Wilda Rochman Hakim; Shofiyullah Muzammil (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
Many assumptions believe that classical Islamic theology is no longer relevant in the contemporary era, either because its discussion tends to be theocentric and far from the progress of humanism or because it is considered no longer relevant to answer contemporary issues such as secularism, pluralism, globalization, or neo-atheism. Departing from these problems, efforts have emerged for new readings of classical theology by paying more attention to the context and needs of the times. Among these efforts is the renewal of theology by highlighting its methodological aspects, as was done by a contemporary Moroccan theologian and philosopher, Ṭahā ‘Abdurraḥmān. This study attempts to describe and analyze the style of renewal of theology from the perspective of Ṭahā ‘Abdurraḥmān. This research is a character study using qualitative methods, in which the existing data is analyzed critically. This article shows that Ṭahā ‘Abdurraḥmān’s style of renewal of ‘ilm al-kalām focuses on efforts to reform the methodology of classical kalam by reforming the method of dialogue science (munaẓarah) through contemporary linguistic and logical tools, rearranging analogy patterns (qiyas), and building a logic of kalam based on the principle’s logic and morality as well as the amalgamation of theoretical aspect and practical aspect. The significance of Ṭahā ‘Abdurraḥmān’s renewal in contemporary Islamic theology lies in the theorizing of concepts in classical theology with a contemporary approach as well as the construction of the methodology of contemporary Islamic theology to answer ever-evolving theological issues.